Bibliometric Insights into Mental Health Challenges and Innovations in Contemporary Society - Judijanto, Loso; Lesmana, Tera (Eastasouth Institute, 2024)
This bibliometric analysis examines the evolution and current state of mental health research from a comprehensive, data-driven perspective. Using VOSviewer for visual mapping, this study highlights key terms, thematic developments, and influential authors within the field over several decades. The analysis reveals a strong ongoing focus on core issues such as